MODEL OF SEEPAGE FLOW ON THE STABILITY FOUNDATION OF MAIN DAM BULANGO ULU GORONTALO - Nurohim, Dede
The research area is located in Bone Bolango Regency, Gorontalo Province. The Bulango Ulu Dam is designed to be a flood control medium as well as irrigation development which requires a water requirement of around 1164 l/second to achieve an agricultural index of 200% (Gorontalo Agriculture Service, 2018). In determining the design of a dam that has a unique structure because apart from its size scale and various types, the dam also has a specific considerations in hydrological and geological aspects in the field. One of the main causes of dam failure is internal erosion (piping) which has the potential for seepage to the embankment or its foundation. The aims of this study were (1) to determine the seepage conditions in the foundation; (2) knowing the level of piping risk; and (2) determine the stability of the foundation due to groundwater seepage. The method used is a collaboration between geology, hydrogeology and engineering. Based on geological analysis with direct observation in the field and image analysis, the Bulango Ulu Dam is located in a Diorite Bone Rock Formation with the characteristics of diorite – granodiorite rock with high fracture intensity range value 0.8 – 1.4 km/km2 based on fault fracture density analysis and has a hydraulic conductivity value between 2.26E-04 cm/s – 1.26E- 05cm/s. The characteristics of groundwater flow in the dam area also have a central orientation to the main dam with the dominant laminar flow type on the bedrock which is used as the foundation of the main dam. The seepage discharge of the main dam reaches 0.093 m3/s. The amount of seepage still meets the requirements of the stipulation that no more than 1% of the average river discharge entering the dam (Department of Public Works, 2005) is 3.86 m3/s with a discharge rate of 1% Q average from the Mongiloo River. The upstream slope area – As the Dam has a very high seepage potential with a total head value of >60 m and pore water pressure value of >1200 kPa with a piping risk safety factor value of 2.29 & 3.46 respectively (standard safety factor value = 4). Seepage countermeasures at the Bulango Ulu Dam must still be carried out, because even though the seepage capacity value still meets the safe requirements, the safety factor of the piping does not reach the specified standard.